Diagnostic significance of biochemical parameters of blood serum of ponies in obesity - Borovkov, S. B.; Boiko, V. S.; Paliy, A. P.; Borovkova, V. M.; Pavlichenko, O. V.; Gerilovich, I. O. (Regulatory Mechanisms in Biosystems, 2024)
Obesity in ponies has become a serious problem leading to the development of metabolic syndrome, insulin resistance and related diseases. The present paper investigates the effect of obesity on metabolic parameters and hormonal status of ponies, especially on the levels of biochemical markers in blood serum. The study was conducted on 18 ponies divided into two groups: 9 clinically healthy animals and 9 obese animals kept in private stables in Kharkiv. All animals received a balanced diet that met their physiological needs, with free access to water and the outdoors. Blood tests included determination of protein and protein fractions, triglycerides, enzyme activity, and hormone levels, including leptin and insulin, and other metabolic markers. The results showed that obese ponies have a decrease in globulin levels, which indicates a decrease in immunity, as well as an increase in albumin concentration, which suggests a violation of the functional state of the liver. Correlations were found between the levels of cholesterol, thyroid hormones (T3 and T4), and insulin, indicating a general disruption of the endocrine system. The study confirms that obesity in ponies is associated with increased levels of triglycerides, which are markers of insulin resistance. Biochemical tests, including serum insulin levels, are important in diagnosing metabolic syndrome. Fasting serum insulin concentrations or fasting serum glucose concentrations are simple tools for assessing insulin resistance. The study also suggests that a decrease in triglyceride and high-density lipoprotein levels in obese animals may indicate a disruption in lipid metabolism. High-density lipoproteins provide a reverse pathway for cholesterol to flow from tissues to the liver, where it becomes a source for the formation of bile acids, vitamin D and steroid hormones. Normally, fatty acids, monotriglycerides, and cholesterol are absorbed by intestinal epithelial cells, but this process may be impaired in obese animals. The data obtained emphasize the need for regular monitoring of biochemical parameters in ponies, especially in overweight animals, for early detection of metabolic disorders and prevention of the development of serious diseases. The paper is important for veterinary practice as it provides new data on the impact of obesity on the health of ponies and emphasizes the importance of an integrated approach to their maintenance and treatment.